Answer: " m = zC / (C − z) " .
___________________________________
Explanation:
_________________________
Given: 1/C + 1/m = 1/z ; Solve for "m".
Subtract "1/C" from each side of the equation:
____________________________________
1/C + 1/m − 1/C = 1/z − 1/C ;
to get: 1/m = 1/z − 1/C ;
____________________________________
Now, multiply the ENTIRE EQUATION (both sides); by "(mzC"); to get ride of the fractions:
_________________
mzC {1/m = 1/z − 1/C} ;
to get: zC = mC − mz ;
Factor out an "m" on the "right-hand side" of the equation:
zC = m(C − z) ; Divide EACH side of the equation by "(C − z)" ; to isolate "m" on one side of the equation;
zC / (C − z) = m(C − z) / m ; to get: 24/8 = 3 24
zC/ (C − z) = m ; ↔ m = zC/ (C − z) .
___________________________________________________
Answer:
I don't know what's I don't know I'm really sorry very very very very very very very very very very very very sorry very sorry
Did you get the answer me and you need help and no one dont want to help i hope you found the answer because i really need it math is very hard.